Novel Insights Into Sterol Uptake and Intracellular Cholesterol Trafficking During Eimeria bovis Macromeront Formation - Silva, Liliana M. R.; Velásquez, Zahady D.; López-Osorio, Sara; Hermosilla, Carlos; Taubert, Anja (Frontiers in Cellular and Infection Microbiology, 2022)
Apicomplexan parasites are considered as defective in cholesterol synthesis. Consequently, they need to scavenge cholesterol from the host cell by either enhancing the uptake of extracellular cholesterol sources or by upregulating host cellular de novo biosynthesis. Given that Eimeria bovis macromeront formation in bovine lymphatic endothelial host cells in vivo is a highly cholesterol-demanding process, we here examined host parasite interactions based on host cellular uptake of different low-density lipoprotein (LDL) types, i. e. of non-modified (LDL), oxidized (oxLDL) and acetylated LDL (acLDL). Furthermore, expression of lipoprotein oxidized receptor 1 (LOX-1), which mediates acLDL and oxLDL internalization, was monitored throughout first merogony, in vitro and ex vivo. Moreover, effects of inhibitors blocking exogenous sterol uptake or intracellular transport were studied during E. bovis macromeront formation in vitro. Hence, E. bovis-infected primary bovine umbilical vein endothelial cells (BUVEC) were treated with inhibitors of sterol uptake (ezetimibe, poly-C, poly-I, sucrose) and of intracellular sterol transport and release from endosomes (progesterone, U18666A). As read-out system, the size and number of macromeronts as well as merozoite I production were estimated. Overall, internalization of all LDL modifications (LDL, oxLDL, acLDL) was observed in E. bovis-infected BUVEC but to different extents. Supplementation with oxLDL and acLDL at lower concentrations (5 and 10 µg/mL, respectively) resulted in a slight increase of both macromeront numbers and size, however, at higher concentrations (25-50 µg/mL), merozoite I production was diminished. LOX-1 expression was enhanced in E. bovis-infected BUVEC, especially towards the end of merogony. As an interesting finding, ezetimibe treatments led to a highly significant blockage of macromeront development and merozoite I production confirming the relevance of sterol uptake for intracellular parasite development. Less prominent effects were induced by non-specific inhibition of LDL internalization via sucrose, poly-I and poly-C. In addition, blockage of cholesterol transport via progesterone and U18666A treatments resulted in significant inhibition of parasite development. Overall, current data underline the relevance of exogenous sterol uptake and intracellular cholesterol transport for adequate E. bovis macromeront development, unfolding new perspectives for novel drug targets against E. bovis.